Vancomycin administration: the impact of multidisciplinary interventions. Issue 10 (9th February 2007) - Crowley, R K; Fitzpatrick, F; Solanki, D; FitzGerald, S; Humphreys, H; Smyth, E G
Abstract : Background: The clinical microbiology team observed that patients were not receiving all prescribed doses of vancomycin. Ward staff was confused about ordering and interpreting vancomycin therapeutic drug monitoring (TDM) levels. Aim: To audit the incidence of vancomycin dose omission. To implement a series of interventions to improve vancomycin dose administration, and to repeat the audit process to assess these interventions. Methods: Three prospective audits were conducted to assess the impact of vancomycin TDM on administration of vancomycin. After the first audit, a number of changes in the TDM process were undertaken. After review of the second audit, a senior pharmacist coordinated ward-based pharmacists in assisting staff to interpret levels, and TDM interpretative charts were designed for drug charts. Following the third audit, feedback to hospital management and a plan for ongoing education were undertaken. Results: There was a significant reduction in the number of vancomycin doses held inappropriately in the third (10% (78/782) of prescribed doses) when compared to the first audit (16% (161/1007) of doses) (p<0.01). Of doses that were held inappropriately, there was a significant decrease in doses held for no apparent reason in audit 3 (16% (27/170) of prescribed doses) when compared to audit 1 (25% (69/282) of doses) (p<0.05). Conclusions: The interventions resulted in a 37.5% reduction in inappropriately held vancomycin doses over a one-year period; 10% of doses are still being held inappropriately. This study highlights the difficulties in identifying barriers to change and changing healthcare worker behaviour.